Penerapan metode pembelajaran STAD dalam meningkatkan hasil belajar PAI siswa kelas x SMA Muhammadiyah Mamuju - Aries Fauzan Najib; Basir Basir; Ilham Ilham; Harfiah Herman (Al-Liqo: Jurnal Pendidikan Islam, 2026)
The low learning outcomes of students in Islamic Religious Education (PAI) were caused by the lack of student participation during the learning process. This study aimed to describe the implementation of the Student Team Achievement Division (STAD) learning method and to determine the improvement of students’ learning outcomes in class X at SMA Muhammadiyah Mamuju. This research used a Classroom Action Research (CAR) approach conducted in two cycles, including planning, implementation, observation, and reflection stages. The research subjects consisted of 20 students. Data were collected through observation, tests (pre-test and post-test), and interviews. The data were analyzed descriptively using average scores and the percentage of learning mastery. The results showed that the implementation of the STAD method improved students’ learning outcomes. In the first cycle, only 6 students (33%) achieved learning mastery with an average score of 60.2, while in the second cycle, the number increased to 16 students (76%) with an average score of 78.6. Therefore, the STAD method is effective in improving students’ learning outcomes in Islamic Religious Education.